(untitled) (Revista Latino-Americana de Enfermagem, 2010)
Moist/wet materials stored after autoclaving are considered contaminated and not recommended for use. This study evaluates the maintenance of sterility in moist/wet material after being submitted to steam sterilization and stored for a period of 30 days. Aiming to support decision-making in emergency situations, 40 surgical boxes packed in nonwoven cloth covering Spunbound, Metblouwn, Spunbound (SMS): half (the experimental group) were placed in an autoclave but the drying phase was interrupted, yielding moist/wet materials and the other half (the negative control group) underwent the complete cycle. The external parts of each surgical box were deliberately contaminated with Serratia marcescens and subsequently stored for 30 days. After this period, the boxes' contents were submitted to sterility tests and no growth was observed. The presence of moisture inside the surgical boxes did not interfere with maintaining their sterility.